2020
DOI: 10.1038/s41467-020-14291-3
|View full text |Cite
|
Sign up to set email alerts
|

NPY mediates the rapid feeding and glucose metabolism regulatory functions of AgRP neurons

Abstract: Activation of Agouti-Related Peptide (AgRP)-expressing neurons promotes feeding and insulin resistance. Here, we examine the contribution of neuropeptide Y (NPY)-dependent signaling to the diverse physiological consequences of activating AgRP neurons. NPYdeficient mice fail to rapidly increase food intake during the first hour of either chemo-or optogenetic activation of AgRP neurons, while the delayed increase in feeding is comparable between control and NPY-deficient mice. Acutely stimulating AgRP neurons fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 36 publications
(50 reference statements)
6
68
0
1
Order By: Relevance
“…Although most energy regulatory neurocircuits, such as melanocortin neurons in the ARC, exert their metabolism regulatory function through neuropeptide and neurotransmitter-dependent signaling in their widespread neurocircuitry in a conventional way by synaptic transmission ( Betley et al., 2015 , Engström Ruud et al., 2020 , Fenselau et al., 2017 , Steculorum et al., 2016 ), MCH neurons have previously been shown to exert at least part of their metabolism regulatory function through additional mechanisms. First, they densely innervate the ependymal cells of the ventricle to regulate cilia beating and CSF circulation ( Conductier et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although most energy regulatory neurocircuits, such as melanocortin neurons in the ARC, exert their metabolism regulatory function through neuropeptide and neurotransmitter-dependent signaling in their widespread neurocircuitry in a conventional way by synaptic transmission ( Betley et al., 2015 , Engström Ruud et al., 2020 , Fenselau et al., 2017 , Steculorum et al., 2016 ), MCH neurons have previously been shown to exert at least part of their metabolism regulatory function through additional mechanisms. First, they densely innervate the ependymal cells of the ventricle to regulate cilia beating and CSF circulation ( Conductier et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researches have revealed that NPY plays a vital role in the regulation of blood glucose homeostasis in diabetic models ( 119 ). The ability of AgRP neurons to induce insulin resistance depends on the expression of NPY ( 120 ), and the application of NPY in the CNS has been shown to efficiently reduce sympathetic activation of BAT and improve systemic insulin sensitivity ( 8 , 107 ). Therefore, the NPY-dependent regulation of systemic insulin sensitivity is consistent with reducing energy expenditure in mice under fasting conditions, possibly by regulating the sympathetic activation of BAT.…”
Section: Npy Indirectly Regulates the Immune Responsementioning
confidence: 99%
“…These two neuronal populations form neural circuits with various hypothalamic target sites such as the lateral (LHA), and paraventricular (PVH) nucleus as well as with extrahypothalamic nuclei including the bed nucleus of the stria terminalis (BNST), amygdala (AMY), lateral parabrachial nucleus (LPB), periaqueductal grey (PAG), the nucleus of the solitary tract (NTS) and the intermediolateral cell column of the spinal cord (IML) ( Fig. 1 ) [ 8 , 15 , 19 , 30 , 65 , 66 , 93 , 123 , 124 , 128 , 170 , 173 , 182 , 192 ].These neuronal circuit connections are crucial for the proper regulation of feeding behavior, energy homeostasis, and glucose metabolism [ 9 , 19 , 67 , 84 , 115 , 129 , 178 , 187 , 195 ].…”
Section: The Arcuate Nucleus: Pomc and Npy/agrp Neuronsmentioning
confidence: 99%
“…Interestingly, the ARH POMC neuron induced reduction of food intake and body weight requires melanocortin receptor signaling [ 9 ] while the AgRP neuron induced hyperphagia is independent of melanocortins [ 9 , 45 , 130 ]. As AgRP is an inverse agonist of melanocortin receptors, these studies highlight the role of NPY and GABA, independent of melanocortin signaling, for the acute ability of AgRP neurons to regulate feeding [ 45 , 58 , 67 , 199 202 ].…”
Section: The Arcuate Nucleus: Pomc and Npy/agrp Neuronsmentioning
confidence: 99%